Bandwidth Enhancement of 5G Parallel Coupled Line Band Pass Filter Using Patterned Ground Structure Technique - Morshidi, Ummi Haziqah; Abang Zaidel, Dyg Norkhairunnisa; Seman, Norhudah; Attan, Melvin Philip; Awang Mat, Dayang Azra; Mohd Sharip, Mohd Ridhuan; Kanaya, Haruichi (International Journal of Integrated Engineering, 2020)
This paper presents the design of parallel coupled line band pass filter with 10 GHz operating frequency that will be used in 5G applications. As 5G application requires big data usage and to cater the applications, the bandwidth of 5G devices need to be wider enough to support it. Thus, to improve the bandwidth performance of the designed filter, patterned ground structure (PGS) technique is implemented into it. The result shows that the bandwidth of the designed filter has been improved from 0.25 GHz to 4.98 GHz when PGS is implemented.